Effects of Incorporating Measured Leaf Optical Properties in Land Surface Models - Dong, Wenzong; Yuan, Hua; Zhang, Ruqing; Li, Hongmei; Huang, Lina; Zhu, Siguang; Peng, Jingman; Dai, Yongjiu (Frontiers in Earth Science, 2021)
Leaf optical properties (LOPs, i.e., leaf reflectance and transmittance), as a fundamental property of vegetation, are a key parameter in the canopy radiative transfer process. LOPs have a direct impact on the surface solar radiation partition and further affect surface flux exchanges. Recent works have provided reliable LOP data and mentioned that notable differences exist between the prescribed LOP values in current land surface models and measured LOP values, especially in the near-infrared (NIR) band. To evaluate the effects of different LOP values in land surface modeling, we ran two land surface models (the Community Land Model and the Common Land Model) with their default prescribed and measured values to examine the differences in simulated surface radiation partitions and fluxes. Our analyses show that differences in LOP values can lead to a large discrepancy in albedo, radiation partition, sensible heat flux and net radiation simulations. By using the measured LOP values, in the boreal forest zone, Southeast China, and the eastern United States, both models have a significantly increased surface albedo in the NIR band, with the difference exceeding 10% during JJA. Thus, the measured LOP values can improve the negative albedo bias in the boreal forest zone during summertime. Moreover, both models simulate less net radiation with a maximum reduction of 11 W/m2 when incorporating the measured LOP values. Therefore, the total sensible heat flux can be reduced by as much as 11 W/m2. The results of this study emphasize that different LOP values can have a considerable effect on the surface radiation budget and sensible heat flux simulations which need attention in land surface model development. However, in current offline simulations, the measured LOP values cause slight changes in land surface temperatures and gross primary productivity (GPP).